Prospective evaluation of rapid point-of-care tests for the diagnosis of acute leptospirosis in dogs. (July 2018) - Troìa, R.; Balboni, A.; Zamagni, S.; Frigo, S.; Magna, L.; Perissinotto, L.; Battilani, M.; Dondi, F.
Highlights: Evaluation of the performances of two in-clinic tests for canine leptospirosis. Positive results on the in-clinic tests are highly suggestive of infection. Negative results need further diagnostic investigation to exclude the infection. Abstract: The early diagnosis of acute leptospirosis is still a major challenge in dogs. The aim of this prospective study was to evaluate the suitability of two in-clinic tests detecting anti-leptospiral IgM and IgG antibodies in diagnosing canine leptospirosis. The performances of the two rapid tests were compared to the microscopic agglutination test (MAT) carried out on acute sera and to diagnostic criteria adopted in this study to confirm leptospirosis infection (MAT upon admission, convalescent MAT and quantitative real-time PCR on blood and/or urine). The dogs were enrolled on the basis of reported exposure to known risk factors and clinical presentation (acute kidney injury and/or systemic inflammatory response syndrome with multi-organ damage). Eighty-nine dogs included in the study were sub-grouped on the basis of the results of the diagnostic criteria adopted: (1) confirmed leptospirosis cases (42/89 dogs); (2) negative leptospirosis cases (36/89 dogs); and (3) unconfirmed leptospirosis cases (11/89 dogs). The results supported the usefulness of the two rapid diagnostic tests as a first in-clinic screening tool for suspected leptospirosis; positive results in the in-clinic tests in dogs with suggestive clinical and laboratory signs strongly indicated acute leptospirosis, while negative results required additional diagnostic investigation to exclude the infection. Confirmatory tests recommended for canine leptospirosis are still necessary in addition to the use of rapid in-clinic tests.